SISTEM PAKAR DETEKSI PENYAKIT LAMBUNG MENGGUNAKAN METODE FORWARD CHAINING DAN CERTAINTY FACTOR BERBASIS WEBSITE - Henry Chris Ravindra; Wiji Setiyaningsih; Gaguk Susanto (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2026)
Stomach diseases are common digestive disorder among Indonesians and are often not treated properly due to increasingly modern lifestyles. According to the WHO, the prevalence of gastritis in Indonesia is 40.8%, while the prevalence of dyspepsia varies from 7% to 45%. The Malang City Statistics Agency and the Malang City Health Office have placed Malang City among the top 10 cities in 2023 for stomach disease cases, with a total of 4,218 cases of gastritis and 4,637 cases of dyspepsia. In the last three years, 40% of patients had stomach problems, 25% had diabetes, and 20% had heart disease. One of the challenges in treating patients with stomach disease is the treating patients with stomach diseases is the similarity of symptoms with other diseases such as appendicitis. In addition, limited access to health services and financial constraints in seeking treatment are the causes of delays in disease management. This study aims to develop an Early Detection System for Stomach Diseases Using Forward Chaining and Certainty Factor, which can assist in the initial diagnosis and early detection of stomach diseases for patients or the community. This system was developed using a waterfall approach model with PHP programming language and MySQL as the database. The results of this system are able to provide diagnoses for 10 types of stomach diseases with a percentage of certainty factor. The results of black box testing are in accordance with the system design and requirement analysis, and the results of user acceptance testing received score of 81.03%.